2015
DOI: 10.3748/wjg.v21.i5.1621
|View full text |Cite
|
Sign up to set email alerts
|

Lesion discrimination with breath-hold hepatic diffusion-weighted imaging: A meta-analysis

Abstract: Breath-hold DWI is useful for differentiating between malignant and benign hepatic lesions. The diffusion characteristics of benign lesions that mimic malignant ones have rarely been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
0
24
1
Order By: Relevance
“…Previous papers highlighted a significant overlap between the ADC value of benign solid FLLs (such as FNH and HCA) and malignant FLLs [26,27]. Our series shows a slight difference between the mean ADC values for NFHs (1036), not significantly higher than the mean ADC value for malignant FLLs (953).…”
Section: Inter-observer Variabilitycontrasting
confidence: 49%
See 2 more Smart Citations
“…Previous papers highlighted a significant overlap between the ADC value of benign solid FLLs (such as FNH and HCA) and malignant FLLs [26,27]. Our series shows a slight difference between the mean ADC values for NFHs (1036), not significantly higher than the mean ADC value for malignant FLLs (953).…”
Section: Inter-observer Variabilitycontrasting
confidence: 49%
“…3). The signal intensity of hemangiomas on the ADC map is slightly lower than the signal of biliary cysts [25,26].…”
Section: Inter-observer Variabilitymentioning
confidence: 84%
See 1 more Smart Citation
“…There has been promising evidence that ADC may be a viable tool to help discriminate benign versus malignant character of a hepatic lesion [ 1 , 6 , [8] , [9] , [10] , [11] , [12] , [13] ]. However, there have been conflicting reports in literature regarding the usefulness of DWI in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, two earlier meta-analyses showed that DWI had high sensitivity (81% and 93%) for detecting HCCs[13,36]. We speculate that the reasons for the difference in the rate of sensitivity between our results and those of the two prior meta-analyses might be related to patient selection bias, the background of liver parenchyma in patients with chronic liver disease (cirrhotic or not), and/or the tumor characteristics ( e.g ., tumor size and malignant grade)[13,36]. …”
Section: Discussionmentioning
confidence: 89%